Surface modification of the γ-TiAl alloys by the nitridation - Sopunna K. (2014)
The nitridation of Ti-47%Al-2%Nb-2%Cr (MJ12) and Ti-47%Al-2%Nb-2%Mn-0.8% TiB2 (MJ47) was studied using purified NH3. The flow rate of the gas was kept constant at 10 mls-1. The nitridation process was done at temperatures of 800, 900 and 1000 °C for 36.0 ks (10 h). The alloys were then characterized using a scanning electron microscope (SEM), an X-ray diffractometer (XRD), a tribometer and a microhardness tester. The Knoop hardness (HK) values of the nitrided alloys were increased with an increase in the nitridation temperature and time. The HK values of MJ12 and MJ47 with 1000 °C nitridation for 36.0 ks were 2.1 and 1.5 times that of the non-nitrided alloys, respectively. The wear rates of MJ12 and MJ47 with 800-1000 °C nitridation were reduced by one or two orders of magnitude in comparison to the non-nitrided alloys. Hardness and wear resistance of the alloys were successfully improved by the nitridation which was in agreement with the formation of the TiN on the alloy surfaces. The SEM micrographs of the nitrided alloys showed a rough surface which could effect the wear resistance. © 2004 Elsevier B.V. All rights reserved.